1974
DOI: 10.1016/0033-5894(74)90007-6
|View full text |Cite
|
Sign up to set email alerts
|

Quaternary Sea Level Fluctuations on a Tectonic coast: New 230Th/234U Dates from the Huon Peninsula, New Guinea

Abstract: Emerged coral reef terraces on the Huon Peninsula in New Guinea were reported in a reconnaissance dating study by Veeh and Chappell 1970. Age definition achieved was not good for several important terraces, and we report here a series of new 230Th/234U dates, which further clarify the history of late Quaternary eustatic sea level fluctuations. More than 20 reef complexes are present, ranging well beyond 250,000 yr old: we are concerned with the seven lowest complexes. Major reef-building episodes dated by 30Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
220
2
8

Year Published

1985
1985
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 639 publications
(238 citation statements)
references
References 19 publications
8
220
2
8
Order By: Relevance
“…Dates for terraces corresponding to our events 5.1 (79,250 yr; stage 5a), 5.33 (103,290 yr; stage 5c), and 5.51-5.53 (122,560-125,190 yr; stage 5e) have been given for New Guinea (Bloom et al, 1974): 82,000, 103,000, and 124,000 yr; Barbados (Fairbanks and Matthews, 1978): 82,000, 105,000, and 125,000 yr; and Haiti (Dodge et al, 1983): 81,000, 108,000, and 130,000 yr. Mix and Ruddiman (1986, Fig . 3) show the last glacial maximum (our event 2.2; 17,850 yr) having a i4C age ranging from 13,000 to 19,000 yr.…”
Section: Discussionmentioning
confidence: 99%
“…Dates for terraces corresponding to our events 5.1 (79,250 yr; stage 5a), 5.33 (103,290 yr; stage 5c), and 5.51-5.53 (122,560-125,190 yr; stage 5e) have been given for New Guinea (Bloom et al, 1974): 82,000, 103,000, and 124,000 yr; Barbados (Fairbanks and Matthews, 1978): 82,000, 105,000, and 125,000 yr; and Haiti (Dodge et al, 1983): 81,000, 108,000, and 130,000 yr. Mix and Ruddiman (1986, Fig . 3) show the last glacial maximum (our event 2.2; 17,850 yr) having a i4C age ranging from 13,000 to 19,000 yr.…”
Section: Discussionmentioning
confidence: 99%
“…They have been dated previously at 125.7 and 123.0 ka BP . Samples KWA-Q-1, FRT-F-1 and SIAL-E-1 are from the Huon Peninsula, Papua, New Guinea (Chappell 1974;Bloom et al 1974). All of the samples were well preserved, with corallites intact.…”
Section: Methodsmentioning
confidence: 99%
“…Modern carbon could be introduced during recrystallization of the coral, or from the addition of modern calcite as over- (Bloom et al 1974) growths on the coral framework. Matthews (1968) has shown that the diagenesis of coral from Barbados depends on kinetic factors and climate.…”
Section: Modern Contamination In Old Coralmentioning
confidence: 99%
“…During this regressional period, valleys were enlarged along the barrier. The sea-Ievel curve of Chappell (1974) and Bloom et al (1974) shows a major regression al period between 220 000 and 160000 years B.P., with a small transgression at 180000 years B.P., and a possible transgression at 200000 years. Assuming Chappell's (1975) uplift rate of 0.3 mm/year for the North Kaipara area, local relative sea levels during the minima would have been about -55 m at 205000 years, -69 m at 190000 years, and -118 m at 160000 years B.P.…”
Section: Pareotaunga Formation (New)mentioning
confidence: 99%